Trading without meeting friends: Empirical evidence from the wuhan lockdown in 2020 - Huang, Yichu; Bose, Udichibarna; Li, Zeguang; Liu, Frank Hong (Journal of Banking & Finance, 2025)
Using a unique proprietary dataset of daily mutual fund trading records and the COVID-19 pandemic-triggered lockdown in Wuhan (China) as a natural experiment, we find that individual mutual fund investors in Wuhan significantly reduced their daily trading frequency, total investment of their portfolios, and risk level of their invested funds during the lockdown period as compared to investors in other cities. The results suggest that the elimination of face-to-face interaction among individual investors during the lockdown reduced their information sharing, which led to more conservatism in their financial trading. We rule out alternative explanations of salience bias due to limited investor attention and temporary changes in personal circumstances such as depression and/or income reduction, during the lockdown period. Finally, consistent with the theory of naïve investor trading, we also find that investors received higher trading returns during the lockdown as they reduced trading aggressively in the absence of face-to-face interactions.